892 Validation of Docetaxel as a Radiosensitizer in High-Risk Meningiomas Based on DNA Methylation Profiling. (April 2023) - Youngblood, Mark W.; Tran, Anh; Wang, Wenxia; An, Shejuan; Scholtens, Denise; Zhang, Lyndsee; O'Shea; Jenny Pokorny, Kaitlyn; Magill, Stephen; Sachdev, Sean; Lukas, Rimas Vincas; Ahmed, Atique; Unruh, Dusten; et al.
Abstract : INTRODUCTION: Genome-wide methylation profiling has emerged as a transformative prognostic tool in meningiomas, and has identified discrete epigenetic clusters that share distinct clinical and biological features. The association of these signatures with underlying pathological mechanisms has not been well-explored. METHODS: From a collection of over two-hundred well-annotated tumors, we found 981 genes in which methylation signal was predictive of recurrence. Using pathway enrichment analysis, Docetaxel was identified as a candidate therapeutic agent; a medication that is frequently utilized in other common malignancies. This chemotherapy was validated in vitro and in vivo using patient derived meningiomas, and also tested in combination with radiotherapy. RESULTS: Based on 15 patient-derived cultures from our institution and 2 public cell lines, we found that Docetaxel could inhibit meningioma growth at concentrations that were favorable relative to other cancers. This drug triggered apoptosis in meningiomas of all tumor grades and methylation classes, with IC50 values ranging from 0.8 nm to 4.4 nm in vitro. Combining Docetaxel with radiation therapy resulted in synergistic cytotoxic effects on meningioma cultures, associated with elevated markers of cell death and dsDNA breaks. We confirmed our results via orthotopic meningioma models of the cell lines CH157 and IOMM-Lee, which exhibited dose-dependent improvements in mortality and tumor volume in response to Docetaxel and radiation. CONCLUSIONS: Our results leverage DNA methylation patterns to repurpose FDA-approved medications in the treatment of meningiomas, and suggest a clinical trial of Docetaxel with radiotherapy may be efficacious in aggressive lesions.